CULT TO THE YLLAS IN HUÁNUCO PAMPA: BETWEEN THE MOON AND THE PUQUIAL - Ordóñez Inga, Carlo (2013)
This article shows evidences of an ancestral cult related with the yllas found between some families located around the Huanuco Pampa site. The record was realized in 2007 and 2012, during the execution of the project Huanuco Pampa - Programa Qhapaq Nan by the Ministry of Culture. The methodology of this research consisted of interviewing to the community, who had the yllas, and then the information collected was contrasted with the revision of the ethno-historical data, in order to demonstrate some continuity of this ritual related with the husbandry of camelids at the incas time and the husbandry of bovines and ovines at present day.